Implementing Peer-to-Peer Technology Training - Ellis, Christopher D. (Valdosta State University, 2002)
The purpose of this study was to determine of peer-to-peer technology training would be a viable option to traditional staff development. On-site, peer "experts" conducted the training over a period of four and one-half weeks. Two mentors and three protégés completed the training. This study utilized pre- and post- intervention surveys, participant portfolios, participant reflective journals, and structured interviews to provide data. In addition, the research sought to examine the experiences of the participants involved. Results suggest that this type of training can be more effective than traditional methods. Participants noted that the individualized nature of the training, which allowed learners to have input as to what would be taught, contributed greatly to the effectiveness of the training. Having access to on-site support was also an important factor in the training's success. Implications for future study include continued study, as well as planning for peer-to-peer staff development, using a slightly different training structure.
Keywords: peer-to-peer; technology training; staff development; Educational technology; Teaching--Aids and devices; Computer-assisted instruction